Need Analysis of Doctoral Students for Academic Services to Support Timely Completion of Studies of Islamic Religious Education at the Postgraduate Program of IAIN Curup - Sutarto Sutarto; Dewi Purnama Sari; Murni Yanto; Desfitranita Desfitranita (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2025)
This research aims to analyze the needs of IAIN Curup Postgraduate Islamic Religious Education Doctoral Program students regarding academic services provided by lecturers and education staff to support the completion of studies on time. The type of research used is qualitative with a case study approach. 21 Islamic Religious Education Doctoral Program (S3) students were the research informants. Data collection was carried out using semi-structured interviews. The validity of the data was checked by source triangulation and interview expansion. The data obtained were analyzed using spiral model analysis. The research results show that students' needs for academic services from lecturers cover three aspects, namely learning services, mentoring and dissertation testing. Students also need academic services from education staff to support completing their studies on time. The lecturers students need are those who can teach, guide, and test professionally. Likewise, academic services provided by education staff must be carried out professionally, reflected in the quality and attitude of providing services.